Produksi Protein Sel Tunggal dari Kultur Saccharomyces cerevisiae dengan Medium Limbah Kulit Nanas (Ananas comosus L. MERR) - Krisna Juniharta Napitupulu; Yayuk Putri Rahayu; Haris Munandar Nasution; Minda Sari Lubis (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Single cell protein is the term used for peoteins derived from microbes such as fungi. Pineapple waste is one of the alternative media that has easiest source of carbohydrates to obtain, so it has the potential for the growth of Saccharomyces cerevisiae. The purpose of this study was to determine wether pineapple waste could produce single cell protein production by adding nutrients to the fermentation medium. The research used in this research is experimental research. To determine the relationship between the independent variable and the dependent variable. Where the independent variables are the addition of nutrients and fermentation time on days 0,2,4,6 to see the dependant variable, namely the analysis of protein content, dry weight analysis of cells, analysis of glucose levels, pH and temperature analysis. The results of this study showed that the highest protein content was obtained in H4 fermentation by MFKN2, namely 0,43%, cell dry weight 0,851 grams, glucose content 1,3402%, ph 4,5, temperature 27,1 ⁰C. Meanwile, MFKN1 showed the highest protein content in H6 fermentation, namely 0,38%, cell dry weight 0,817 grams, glucose content 1,3397%, pH 4, temperature 26,2 ⁰C. The yield of glucose and pH tended to decrease as the fermentation process progressed until the last day of fermentation. The results of the temperature analysis tend to be stable as the fermentation process progresses until the last day of fermentation. The conclusion of this study is that pineapple waste can produced single cell protein from Saccharomyces cerevisiae culture and has different protein production with the addition of nutrients in the fermentation medium.